Improvement of Latex Quality Using Locally-Produced Organic Fertilizer from Rubber Processing Sewage Sludges - Riwandi Riwandi; Prasetyo Prasetyo; Hasanudin Hasanudin; Indra Cahyadinata; Ali Munawar; Rachma Doni (UNIVERSITY OF LAMPUNG, 2017)
Most of rubber plants in Indonesia are cultivated in highly-weathered soils; therefore, their annual productions are relatively low with the low quality of latex. The aim of this reseach was to increase the latex quality from a rubber plantation grown on low fertility soils by applying a locally-produced organic fertilizer (LOF) to the soils. This research consisted of two steps, i.e. LOF production and a field fertilization experiment. The LOF was made mainly from waste of a latex processing industry. The field fertilization experiment was conducted to assess the effects of LOF additions to the soils on the latex quality. The field experiment was performed using a randomized complete block design with 6 LOF levels, 4 levels of land slopes, and 5 rubber trees in each block, resulting in 120 rubber trees. The LOF levels were 0, 10, 20, 30, 40, and 50 kg tree-1. The LOF contained 17.35% organic-C, 1.14% total-N, 0.53 ppm available-P, and 1.21 cmol (+)kg-1 exchangeable-K, with slightly alkaline pH (pH 8.0). The soil has low fertility status as indicated by the low amounts of total-N and exchangeable base cations (K, Na, and Mg), and very acid pH (pH 4.5). Indicators of latex quality comprising of blockage index, ash-, impurity- and dry rubber-content, and N, P, K contents in the rubber leaves were measured. Although there were no significant differences in most observed latex properties due to LOF addition, their values tended to be higher when the rubber trees were fertilized with LOF. Apparently N and K contents in the rubber leaves are better correlated to the latex properties compared to the P content.